Correlations among somatic cell count, hygienic safety and quality of milk of primiparous cows - Adamov Nikola; Petkov Vladimir; Atanasov Branko (Macedonian Veterinary Review, 2009)
In this work we examined a total of 518 milk samples on the following parameters: somatic cell count (SCC), total bacteria count (CFU and IBC), fat, protein, lactose and dry matter non fat (DMNF) contents, which were obtained from primiparous cows divided in three groups depending on the stage of lactation: the first group included the primiparous cows that were 10-100 days in lactation, the second group 101-200 days in lactation and the third group 201 and more days in lactation. The somatic cell count and the total bacterial count had highest values for the first group, intermediate for the third group, and lowest for the second group with these differences being statistically significant. Milk component contents varied among groups differently from previous two parameters but their differences were not significant in neither case. The somatic cell count of all three groups was positively and significantly correlated to the bacterial counts while these two parameters were generally in negative correlation with the milk component contents. No matter if the parameters that define the milk hygienic safety were positively or negatively correlated with the milk component contents, the correlation coefficients were not significant in neither case, which implies that significant reduction of milk components can be expected at somatic cell counts higher than the maximal obtained in this research of 236.000 SCC/ml.